The Rediscovery of Common Sense Philosophy - Boulter, S. author. aut Link
XVI, 237 p.
Keywords: This book is a defence of the philosophy of common sense in the spirit of Thomas Reid and G.E. Moore, drawing on the work of Aristotle, evolutionary biology and psychology, and historical studies on the origins of early modern philosophy. It defines and explores common sense beliefs, and defends them from challenges from prominent philosophers.